Changes in the provision of psychiatric beds and incarceration in the Eastern Mediterranean Region from 1990 to 2022 - Mundt, Adrian P.; Paiman, Mohammad Akbar; Dalky, Heyam; El-Khoury, Joseph; Ghuloum, Suhaila; Mohammed, Mohammed; Delhey-Langerfeldt, Sabine; Fekih-Romdhane, Feten; Elsabbahy, Medhat; Marie, Mohammad; Saleh, Maan; Priebe, Stefan; et al. (Frontiers in Psychiatry, 2025)
BackgroundPsychiatric bed numbers (general, forensic, and residential) and prison populations are considered indicators of institutionalization. The present study aimed to assess trends in institutional mental health care and incarceration, measured through psychiatric bed availability and prison population rates, across the Eastern Mediterranean Region (EMR) from 1990 to 2022.MethodsWe obtained retrospective data on psychiatric bed numbers and prison populations from 22 countries between 1990 and 2022. Prevalence per 100,000 population, the median prevalence and percentage changes between the first and last data points were calculated.FindingsPrimary data were retrieved from 10 out of 22 countries. Data from secondary sources were used for the remaining 12 countries. In Libya and Somalia, primary data were only available for the prison populations. The median prevalence of psychiatric beds decreased from 8.8 to 5.8 per 100,000 population (-35%) between 1990 and 2022. An increase from 0.2 to 0.4 in forensic psychiatric beds was observed. The prevalence of beds in residential facilities was available from seven countries, two of which did not have beds between 1990 and 2022. The median rates increased from 0.1 to 0.2 between 1990 and 2022. The median prison population also increased from 86.9 to 108.0 per 100,000 people (+24%).InterpretationEMR countries showed, on average, a reduction in the prevalence of psychiatric beds from low numbers, while more people were imprisoned over the past three decades. The availability of forensic psychiatric beds and residential facilities has remained limited. These findings suggest a gradual shift in the EMR from institutional psychiatric care toward increased reliance on incarceration, paralleling trends observed in other global regions like Latin America and Central Eastern Europe and Central Asia.